Resting State Functional Connectivity of Brain With Electroconvulsive Therapy in Depression: Meta-Analysis to Understand Its Mechanisms - Sinha, Preeti; Joshi, Himanshu; Ithal, Dhruva (Frontiers in Human Neuroscience, 2021)
Introduction: Electroconvulsive therapy (ECT) is a commonly used brain stimulation treatment for treatment resistant or severe depression. This study was planned to find the effects of ECT on brain connectivity by conducting systematic review and coordinate based meta-analysis of the studies performing resting state fMRI (rsfMRI) in patients with depression receiving ECT. Methods: We searched systematically the databases published up to 31st July 2020 for the studies in patients having depression that compared resting-state functional connectivity (rsFC) before and after a course of pulse wave ECT. Meta-analysis was performed using the activation likelihood estimation method after extracting details about coordinates, voxel size and method for correction of multiple comparisons corresponding to the significant clusters, and respective rsFC analysis measure with its method of extraction. Results: Among 41 articles selected for full-text review, 31 articles were included in systematic review. Among them, 13 articles were included in meta-analysis, where a total of 73 foci of 21 experiments were examined using activation likelihood estimation in 10 sets. Using cluster level interference method, one voxel-wise analysis with the measure of amplitude of low frequency fluctuations (ALFF) and one seed-voxel analysis with right hippocampus showed significant reduction (p< 0.0001) in left cingulate gyrus (dorsal anterior cingulate cortex), and significant increase (p< 0.0001) in right hippocampus with right parahippocampal gyrus respectively. Another analysis with the studies implementing network-wise (posterior default mode network- dorsomedial prefrontal cortex) resting state functional connectivity showed significant increase (p< 0.001) in bilateral posterior cingulate cortex. There was considerable variability as well as few key deficits in preprocessing and analysis of neuroimages, and the reporting of results in the included studies. Due to lesser studies, we could not do further analysis to address the neuroimaging variability and subjects related differences. Conclusion: The brain regions noted in this meta-analysis are reasonably specific and distinguished, which had significant change in resting state functional connectivity after a course of ECT for depression. More number of studies with better neuroimaging standards should be conducted in future to confirm these results in different sub-groups of depression and with varied aspects of ECT.